INHIBITION OF COX-2 EXPRESSION BY LUNASIN-RICH SOYBEAN EXTRACT ON COLORECTAL CANCER - KUSMARDI, KUSMARDI; KARENINA, VANNESSA; ESTUNINGTYAS, ARI; TEDJO, ARYO (International Journal of Applied Pharmaceutics, 2019)
Objective: The incidence of colorectal cancer has been growing faster than most other cancers in the past decade, especially in developing countries. One of the substances that is currently being investigated as potential chemopreventive agent is lunasin, which is contained in soybeans. This research explored the effect of lunasin on COX-2 expression in the distal colons of mice in which colorectal carcinogenesis was induced with azoxymethane (AOM) and dextran sodium sulfate (DSS). Methods: A total of 30 Swiss Webster mice were separated into six groups. In five of the groups—a negative control group, positive control group, and three intervention groups—carcinogenesis was induced with AOM and DSS; the sixth group received no interventions. Lunasin-rich soybean extracts were given in doses of 250, 300, and 350 mg/kgBW for 6 w to the intervention groups Immunohistochemical staining of COX-2 was then carried out on tissue samples from the distal colons of mice that had been sacrificed. The samples were microscopically assessed and photographed, and cell counts were performed using the Image J application. COX-2 expression is reported in the form of an optical density score (ODS). Results: Significant differences between the negative control and the intervention groups were found at the 300 mg/kgBW (p = 0.047) and 350 mg/kgBW (p = 0.016) lunasin dosage levels. Conclusions: This demonstrates that administration of lunasin-rich soy extracts can inhibit COX-2 expression in cryptic epithelial cells of the distal colon in mice with carcinogenesis induced by AOM and DSS.